Balanced Scorecard as a Comprehensive Approach to Assessing Performance in a Valuation Consulting Company - Aprilatu, Yumas Ressy; Pithendro, Jacinda Nathania; Raharjo, Susilo Toto (Technium Social Sciences Journal, 2025)
This study focuses on a company engaged in valuation consulting services. Currently, the company’s performance evaluation is limited to financial aspects, leading to a short-term profit orientation and overlooking other critical performance dimensions. To address this issue, a comprehensive performance assessment is necessary. This research applies the Balanced Scorecard (BSC) method to evaluate the company's overall performance. Data were collected through observations, interviews, and direct discussions with company personnel. Secondary data, including revenue, project count, and client data over the past five years, was also utilized. Using the Objective Matrix (OMAX) method, the company's overall performance score was calculated at 3.11. This score indicates that while the company has met the minimum performance standards, it has not yet achieved its internal targets. Further analysis using the Objective Matrix and Traffic Light System revealed that out of the evaluated indicators, 2 met the desired standards, 5 were adequate but below target, and 5 remained significantly underperforming. The findings imply that adopting a more balanced and strategic approach to performance management can support long-term growth and operational effectiveness.